2016
DOI: 10.1038/nmicrobiol.2016.185
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome-based population biology and epidemiological surveillance of Listeria monocytogenes

Abstract: Listeria monocytogenes (Lm) is a major human foodborne pathogen. Numerous Lm outbreaks have been reported worldwide and associated with a high case fatality rate, reinforcing the need for strongly coordinated surveillance and outbreak control. We developed a universally applicable genome-wide strain genotyping approach and investigated the population diversity of Lm using 1,696 isolates from diverse sources and geographical locations. We define, with unprecedented precision, the population structure of Lm, dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
815
3
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 563 publications
(900 citation statements)
references
References 45 publications
38
815
3
4
Order By: Relevance
“…The CC4 phylogeny confirms recent results that this CC is associated to clinical strains and is probably one of the most virulent (Maury et al, 2016).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The CC4 phylogeny confirms recent results that this CC is associated to clinical strains and is probably one of the most virulent (Maury et al, 2016).…”
Section: Resultssupporting
confidence: 87%
“…We employed a recently developed Lm cgMLST method by Moura and colleagues (Moura et al, 2016) to assign an allelic designation to the 1,748 loci in the scheme for each of the genomes sequenced. The scheme was implemented using BIGSdb (Jolley and Maiden, 2010).…”
Section: Core Genome Mlst (Cgmlst)mentioning
confidence: 99%
See 1 more Smart Citation
“…These shifts in infectious diseases are caused by the adaptation of microorganisms to changes in human behavior, demographics, and life style (Cascio et al, 2011); changes in economic development and land use (Suhrcke et al, 2011); loss of biodiversity (Swaddle and Calos, 2008;Ostfeld, 2009); global travel (Hufnagel et al, 2004); immigration (Schmid et al, 2008); air conditioning; crowded intensive care units in large hospitals; global environmental and climate changes (Semenza et al, 2012); evolution of susceptible populations, exotic pets, exotic foods and pathogen adaptation (Casadevall et al, 2011;Price et al, 2012); as well as advances in detection techniques Allerberger, 2012;van Doorn, 2014). With industrialization of food processing, worldwide shipment of fresh and frozen food and an increased demand for fresh bagged produce foodrelated outbreaks shifted from local, often family-based, outbreaks to multistate or multicountry outbreaks, often caused by a single source (Shane et al, 2002;Tauxe, 2002;Denny et al, 2007;Nygren et al, 2013;Schmid et al, 2014;Ruppitsch et al, 2015b;Inns et al, 2016). Disease surveillance is an inevitable cornerstone for early identification of infectious disease outbreaks and for timely implementation of accurate measures to combat transmission and morbidity (Johns et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The most immediate field where NGS have been introduced into daily routine diagnostics in microbiology is surveillance and outbreak investigation. Several studies on a variety of bacterial species have already shown that WGS-based typing, based either on single nucleotide variants (SNVs) (Turabelidze et al, 2013;Pightling et al, 2015) or on gene-by-gene allelic profiling of core genome genes, frequently named core genome MLST (cgMLST) or MLST + (Laing et al, 2010;Mellmann et al, 2011;Köser et al, 2012;Maiden et al, 2013;Antwerpen et al, 2015;de Been et al, 2015;Moran-Gilad et al, 2015;Chaudhari et al, 2016;Moura et al, 2016), currently represents the ultimate diagnostic typing tool that have been successfully applied for outbreak investigations (Figure 9) (den Bakker et al, 2014;Schmid et al, 2014;Ruppitsch et al, 2015b; Lepuschitz, 2015). Molecular typing of bacteria for epidemiological surveillance and outbreak investigation Burckhardt et al, 2016;Chen et al, 2016;Jackson et al, 2016).…”
mentioning
confidence: 99%